Uwarunkowania skuteczności programów ograniczających niską emisję na przykładzie jednostek samorządu terytorialnego - Godzisz, Karolina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The monograph analyses the effectiveness of low-emission reduction programs implemented by local government units in the Lubusz Voivodeship. The main objective was to identify relationships between the organizational conditions of municipalities and the effectiveness of implementing environmental measures and obtaining external funding. The study demonstrated that program effectiveness depends, among other factors, on the number and qualifications of employees responsible for environmental protection, the type and size of municipalities, the level of strategic planning, and the financial capacity of local governments.
Keywords: niska emisja; samorząd terytorialny; polityka ekologiczna; ochrona powietrza; województwo lubuskie; fundusze unijne; zrównoważony rozwój; administracja publiczna; low emissions; local government; environmental policy; air protection; Lubusz Voivodeship; EU funds; sustainable development; public administration